2022
DOI: 10.1186/s12951-022-01411-y
|View full text |Cite
|
Sign up to set email alerts
|

Urchin-like magnetic microspheres for cancer therapy through synergistic effect of mechanical force, photothermal and photodynamic effects

Abstract: Background Magnetic materials mediated by mechanical forces to combat cancer cells are currently attracting attention. Firstly, the magnetic force penetrates deeper into tissues than the NIR laser alone to destroy tumours. Secondly, the synergistic effect of nano-magnetic-material characteristics results in a viable option for the targeted killing of cancer cells. Therefore, mechanical force (MF) produced by magnetic nanomaterials under low frequency dynamic magnetic field combined with laser t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…The simultaneous use of photodynamic with MHT also multiplies the effect of these combined treatments due to the PDT-Induced radical toxicity by weaken theheat-shock cellular defense [ 79 , 80 ]. In addition, the dose of the nanoparticle, frequency and magnetic field, light exposure dose used in the combined treatments are much less than individual treatments, and itself helps to maintain healthy tissue in next in vivo studies [ 81 ]. Also these combination therapies showed good effect on reduction of CD44 + CD24 − and CD133 + CD44 + cells which are well-known surface biomarkers of CSCs [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…The simultaneous use of photodynamic with MHT also multiplies the effect of these combined treatments due to the PDT-Induced radical toxicity by weaken theheat-shock cellular defense [ 79 , 80 ]. In addition, the dose of the nanoparticle, frequency and magnetic field, light exposure dose used in the combined treatments are much less than individual treatments, and itself helps to maintain healthy tissue in next in vivo studies [ 81 ]. Also these combination therapies showed good effect on reduction of CD44 + CD24 − and CD133 + CD44 + cells which are well-known surface biomarkers of CSCs [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Wu et al [107], novel hollow magnetic microspheres were synthesized, composed of superparamagnetic Fe3O4, for multimode cancer therapy. Results demonstrated that a combination of NPs, magneto-mechanical force, photothermal, and photodynamic effects under a varying magnetic field and 808 nm laser led to the elimination of nearly all cancer cells, with approximately 99% cell death.…”
Section: Synergistic Magneto-mechanical Effect-pttmentioning
confidence: 99%